Preface of the 3rd International Electronic Conference on Processes (ECP 2024) - Giancarlo Cravotto (Engineering Proceedings)
The 3rd International Electronic Conference on Processes—Green and Sustainable Process Engineering and Process Systems Engineering (ECP 2024) was hosted online from 29 to 31 May 2024 [...]